If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(4y-4)-y=-3(y-4)
We move all terms to the left:
-4(4y-4)-y-(-3(y-4))=0
We add all the numbers together, and all the variables
-1y-4(4y-4)-(-3(y-4))=0
We multiply parentheses
-1y-16y-(-3(y-4))+16=0
We calculate terms in parentheses: -(-3(y-4)), so:We add all the numbers together, and all the variables
-3(y-4)
We multiply parentheses
-3y+12
Back to the equation:
-(-3y+12)
-17y-(-3y+12)+16=0
We get rid of parentheses
-17y+3y-12+16=0
We add all the numbers together, and all the variables
-14y+4=0
We move all terms containing y to the left, all other terms to the right
-14y=-4
y=-4/-14
y=2/7
| 6x=32x | | 7=8x+13 | | 8(s-12)=100 | | 6(s+6)=4s+8 | | 0.75x+0.05(18-x)=0.10(37) | | 2b+6=2b-19 | | 5x+8=7×-8 | | 16y=3.2 | | 40+2x)(30+2x)=3000 | | 28z=5.6 | | 8(4x-x)=7x-2 | | (3a+2)=0 | | 0.25x+2=x-10 | | -15b=-120 | | 48-9=3s+6 | | -338/x=-26 | | 10m—3m+8=43 | | 3x=10(x-56 | | 56=11u-3u | | 3a=326 | | 28=3x=71 | | 14x-6=10x | | x÷12=2 | | 19=5n=7-3n | | 3x+2x+x=270 | | 3x^2-4=-4x | | x2+18x-44=-4 | | 210-5=41790t | | 7y−2=5y+4 | | 4x+3=2x+11-3 | | 25-7x=66 | | t+6÷5=t+2÷10 |